Gold Nanoparticles Synthesized by Geobacillus Sp. Strain id17 a Thermophilic Bacterium Isolated from Deception Island, Antarctica - Blamey-Alegria, J (2013)
Background: The use of microorganisms in the synthesis of nanoparticles emerges as an eco-friendly and exciting approach, for production of nanoparticles due to its low energy requirement, environmental compatibility, reduced costs of manufacture, scalability, and nanoparticle stabilization compared with the chemical synthesis.Results: The production of gold nanoparticles by the thermophilic bacterium Geobacillus sp. strain ID17 is reported in this study. Cells exposed to Au3+ turned from colourless into an intense purple colour. This change of colour indicates the accumulation of intracellular gold nanoparticles. Elemental analysis of particles composition was verified using TEM and EDX analysis. The intracellular localization and particles size were verified by TEM showing two different types of particles of predominant quasi-hexagonal shape with size ranging from 5-50 nm. The mayority of them were between 10-20 nm in size. FT-IR was utilized to characterize the chemical surface of gold nanoparticles. This assay supports the idea of a protein type of compound on the surface of biosynthesized gold nanoparticles. Reductase activity involved in the synthesis of gold nanoparticles has been previously reported to be present in others microorganisms. This reduction using NADH as substrate was tested in ID17. Crude extracts of the microorganism could catalyze the NADH-dependent Au3+ reduction.Conclusions: Our results strongly suggest that the biosynthesis of gold nanoparticles by ID17 is mediated by enzymes and NADH as a cofactor for this biological transformation. © 2013 Correa-Llantén et al.; licensee BioMed Central Ltd.